Stroke performance during butterfly and breaststroke swim at the lowest speed corresponding to maximal oxygen consumption - Ramos, L.; Marinho, D.; Soares, D.; Mota, J.; Figueiredo, J.; Morouco, P.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming X, 2006)
The aim of this study was to analyse if TLim-v v O2max, tested for the first time in breaststroke and butterfly, is also influenced by stroke rate (SR), stroke length (SL) and stroke Index (SI). Ten elite swimmers (7 males of 19.58±2.9 yy, 176.±5.0 cm and 70.5±6.2 kg, and 3 females of 17.6±1.5 yy, 166.3±5.1 cm and 60.9±6.5 kg) performed, in their best simultaneous technique, an intermittent incremental protocol for vO2max assessment. 48 hours late, subjects swam until exhaustion at their predetermined velocity, to assess Tlim-v v O2max., SL=v.SR-1, SR (cycles.min-1) and SI=SL*v. Regarding the relationship between TLim- v v O2max and the different stroke parameters, it was not found any relationship for each technique. However, when both techniques were considered, it was observed an inverse relationship between TLim- vVO2max and SR and between TLim- vVO2max and vVO2max.